Community of Practice, Community of Support : IHE teacher preparation using a servingness professional development model for creating community - Conley, AmyK (Educational (Re)naissance, 2023)
In order to humanize and connect future educators across programs, a Northern California four-year university created a weekly speaker series of professional development, Teachers, Eduleaders, Advocates, and Scholars (TEAS). TEAS aims to connect future educators to current practitioners to better meet the needs of PK-12 students and use a “servingness” model to meet the needs of diverse future educators. While TEAS has been successful at connecting educators across programs and humanizing education, an unexpected benefit has been educators that appear more confident in joining the profession. The next year of TEAS is an opportunity to further study these results.